Assessing the aquatic toxicity and environmental safety of tracer compounds Rhodamine B and Rhodamine WT. (1st June 2021) - Skjolding, L.M.; Jørgensen, L.vG.; Dyhr, K.S.; Köppl, C.J.; McKnight, U.S.; Bauer-Gottwein, P.; Mayer, P.; Bjerg, P.L.; Baun, A.
Abstract: Tracer tests represent a well-established method for delineating key environmental processes in various media and engineered systems. Tracers like Rhodamine B and WT are frequently applied due to their strong fluorescence even at low concentrations.. However, due to a lack of ecotoxicological data, limit values for these tracers cannot be determined. This study fills this critical data gap by providing ecotoxicity data for Rhodamine B and WT using a battery of short-term standardized tests, including growth rate inhibition tests with algae ( Raphidocelis subcapitata ) and lethality tests using crustaceans ( Daphnia magna ) and zebrafish ( Danio rerio ) embryos, and estimating EQS for surface water. For Rhodamine B, the effective and lethal concentration (EC50 and LC50 ) –causing 50% toxicity were in the range of 14–24 mg/L. For Rhodamine WT, no statistically significant effects were observed ( p <0.05) at the tsted concentrations (up to 91, 100 and 200 mg/L for algae, crustaceans and fish embryos, respectively). Thus for all tested organisms, Rhodamine B was more toxic than Rhodamine WT (more than 14 times more toxic for R. subcapitata, 5.6 times for D. magna, 15 times for D. rerio embryos, based on EC10 and LC10 values). These results signify that read-across assessments using ecotoxicity data obtained with Rhodamine B is not advisable for estimating the ecotoxicity of Rhodamine WT. The annual-average quality standard (AA-QS) and maximum allowable concentration quality standard (MAC-QS) for Rhodamine B were found to be 14 and 140 µg/L, respectively. For Rhodamine WT, the corresponding values were estimated to >91 µg/L (AA-QS) and >910 µg/L (MAC-QS). Hence, concentrations below 140 µg/L or 910 µg/L for Rhodamine B and WT, respectively, are not expected to pose a risk to aquatic freshwater life in the case of intermittent discharges, e.g. tracer experiments released in streams.